A política de formação de professores da educação básica no contexto da crise estrutural do capital: o caso MAGISTER/Ceará - Diógenes, Lenha Aparecida Silva (2009)
Investigate the Policy of Teachers Training from Basic Education of Ceará state, in the context of crisis in the capital, focusing on the Program MAGISTER. The research area consisted two universities - UFC and UECE – from four institutions responsible for conducting the Course. For the achievement of this objective, recourse to the literature about the subject, the examination of documentary sources, such as laws, opinions, decrees, resolutions, guidelines, educational proposal, among others, besides interviews with a representative of SEDUC, the Federal University of Ceará and Estadual University of Ceará, players of the establishment and development of MAGISTER Course. The results showed that: a) investment in the training of teachers occupy a prominent place in public policy – Ceará and Brazilian b) the policy of training teachers in Ceará, in 1990, following the guidance of international agencies , focusing in-service training, particularly the methodological aspects of teaching and designing the teacher as a "practical" problem solving, unable to carry out a creative praxis, by being confined to a praxis "reiterative" c) the Program Magister aimed to top-level certification of teachers (public state and municipal), materializing the format defined by international organizations.